Analysis and Improvement of a Robust User Authentication Framework for Ubiquitous Sensor Networks - Ling Chi; Liang Hu; Hongtu Li; Jianfeng Chu (International Journal of Distributed Sensor Networks)
As an infrastructure of the ubiquitous sensor networks, the wireless sensor network plays an important role in generation of multi-networks integrated system. And currently the wireless sensor network is not only being used to monitor and analyze information about the environment but also being used for more dynamic systems. The security system is one of standards for measuring whether a wireless sensor networks is an outstanding wireless sensor network. RUASN proposes a robust user authentication framework for wireless sensor networks, based on a two-factor concept. This proposed scheme possessed many advantages against major existing attacks and performed well at efficiency and low consumption. However, we have identified that the resistance of collusion attacks is weak. After analyzing, we proved that we can obtain the session key via controlling a compromised sensor node and using the collusion attack when a user wants to establish a session with a legal node. Therefore, to enhance the resistance of collusion attacks, we present two ways to solve the security drawbacks of RUASN scheme. One is to add a slight improvement into the RUASN scheme to enhance this scheme. Another is using the Hardware Security Module. After a simple analysis, we have proved that the improved scheme can resist the collusion attack.